(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
Field trials were conducted to evaluate the effect of chemical fertilizers, farmyard manure (FYM) and gypsum on yield and yield components of groundnut (Arachis hypogea L.). There were nine treatments included unfertilized treatment and full doses of recommended NPK fertilizers (65:100:75 kg/ha) or reduced doses of recommended NPK fertilizers (30:50:37.5 kg/ha) and FYM@10 t/ha in combination with different levels (0, 150, 300 and 450 kg/ha) of gypsum. The results exhibited that full dose of NPK fertilizers with 300 kg/ha gypsum treatment gave significantly (P<0.05) higher seed yield (2777.28 kg/ha) than the full dose of NPK fertilizers alone (typical control) which had 2276.05 kg/ha. On the other hand, application of reduced dose of NPK fertilizers + 10 t/ha FYM with 450 kg/ha gypsum resulted 2609.88 kg/ha seed yield followed by 300 kg/ha gypsum application which had 2521.98 kg/ha and both values were statistically similar. Thus, use of 300 kg/ha gypsum could give high seed yield of groundnut with full dose of NPK fertilizers alone or reduced dose of NPK fertilizers and 10 t/ha FYM. However, combined application of organic and inorganic fertilizers is better practice especially on sandy regosol when considering human and soil health. Bangladesh J. Sci. Ind. Res. 51(4), 285-290, 2016